Proceedings of the 9th International Congress on the Archaeology of the Ancient Near East: June 9-13, 2014, University of Basel. Volume 2: Egypt and Ancient Near East - Perceptions of Alterity, Ancient Near Eastern Traditions vs. Hellenization/Romanization, Reconstructing Ancient Eco-Systems, Islamic Session - Bickel, Susanne; Jacobs, Bruno; Le Tensorer, Jean-Marie; Genequand, Denis; Kaelin, Oskar; Mathys, Hans-Peter (Harrassowitz, O, 2016)
Cover -- Title Page -- Copyright -- Contents -- Egypt and Ancient Near East - Perceptions of Alterity -- Ancient Near, Eastern Traditions vs. Hellenization/Romanization -- Reconstructing Ancient Eco-Systems -- Islamic Session -- Raphaël ANGEVIN, Lithic Industries and Interregional Trade between Egypt and the Levant during the 4th Millennium BC: a Review of the Evidence -- Johannes BECKER, The Large-Scale Landscape Paintings of Tell el-Dabca/Egypt -- Johannes JUNGFLEISCH, When Aegean Wall Paintings Meet Egyptian Architecture: Simulations of Architecture from ‹Palace G› at Tell el-Dabca/Egypt